Using Benchlearning for the Improvement of the Institution's Overall Performance - Mircea BĂCALĂ; Diana SALA (Revista de Management Comparat International)
In the present work, we are attempting to explain why Benchlearning is a particularly well adapted method of the contemporary scene and why is it useful in the public institutions' management, as well as to describe in concrete terms what happens during a benchlearning project. Benchlearning is an instrument proposing a formal framework for the public institutions, to learn how to improve things from other similar institutions' good practices, allowing them to become a source of inspiration for their own activity and to learn how to maximize the obtained results and to avoid others' mistakes. The goal of benchlearning is that institutions should learn from the strengths of other institutions and from their working manner, to be inspired and transpose, in their daily activity, elements from these experience exchanges, as well as to learn from others' mistakes and not repeat them. The introduction of this instrument within the Prefect’s Office of Timis County can constitute the corollary of all other modernization instruments applied at institution level, creating a framework to learn from other similar institutions' good practices, to learn how to do things better, to constitute an inspiration source for its own activity and to learn how to avoid the mistakes made by others.